Towards high-performance heterogeneous palladium nanoparticle catalysts for sustainable liquid-phase reactions - Van Vaerenbergh, Beau; Lauwaert, Jeroen; Vermeir, Pieter; Thybaut, Joris W; De Clercq, Jeriffa (Reaction chemistry & engineering, 2020)
High-performance supported palladium nanoparticle (Pd-NP) catalysts help to address the growing demand for 'green' chemical production processes. At present, literature information on how the NP characteristics, NP-support and support-reactant/product interactions affect the catalytic performance, is scattered. As a result, the present review aims to bring together and critically analyze the relevant literature reports on the catalytic performance of supported Pd-NP catalysts in various liquid-phase reactions such as (de-)hydrogenation, alcohol (electro-)oxidation and cross-coupling reactions. The five main NP support classes, i.e. , metal oxides, zeolites, carbon structures, polymers and ordered porous materials, are discussed in detail. A thorough understanding about the catalytic behaviour of supported Pd-NP catalysts via the NP characteristics, NP-support and support-reactant/product interactions give useful insights to optimize current or even create novel NP catalysts for a specific liquid-phase reaction. A walk-through of nanoparticle-reactant/product, nanoparticle-support and support-reactant/product interaction effects on the catalytic performance of heterogeneous palladium catalysts in liquid-phase reactions.